Ao haru ride. 5 - Sakisaka, Io (Shojo beat manga., 2019)
"Futaba Yoshioka has encountered her first love again in high school, but he seems different from the boy she once knew... Kou asks Futaba to go on a date with him to the summer festival. But as the two grow closer, fellow student Toma Kikuchi sets his sights on Futaba."--Provided by publisher.